Profile of Pulmonary Tuberculosis After COVID-19 at Toba District, North Sumatra Province - Simatupang, Elvando Tunggul Mauliate; Simanjuntak, Arya Marganda; Yovi, Indra; Simbolon, Rohani Lasmaria; Fauzi, Zarfiardy Aksa (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Worldwide cases of pulmonary tuberculosis (PTB) have significantly increased since the COVID-19 pandemic. Indonesia accounted for 6,811,818 of the 767,518,723 cases reported by the World Health Organization. While the Indonesian Ministry of Health reported 824,000 cases, the Global Tuberculosis Report in 2022 reported 10.6 million cases. The pandemic has hampered the goal of eliminating PTB globally, with cases diagnosed after COVID-19 having a 7.15-fold increased risk of contracting the illness.Methods: This cross-sectional study was conducted using total sampling to identify the profile of patients with PTB after having COVID-19 based on age, gender, classification, and type of PTB, as well as the duration of occurrence of PTB after COVID-19. The data collected were from COVID-19 patients from 2020 to 2022, then compared with PTB data. All data were compared to ensure that COVID-19 and PTB patient data were the same.Results: Of the 2544 patients recorded, 29 (1.1%) were infected with PTB after COVID-19 infection. The mean age of patients was 34±18.9 and was dominated by men (68.9%). Most of the cases were drug-sensitive TB (96.6%) and clinically diagnosed TB (55.2%). Age had a statistically significant association with the occurrence of TB cases after COVID-19 infection (P<0.0001). The mean time from the initial diagnosis of COVID-19 to the diagnosis of confirmed TB was approximately 203±34.3 days (6.7 months).Conclusion: After COVID-19, patients have the potential to be infected with TB. Screening former COVID-19 patients can be one solution to finding early cases of PTB.